2023
DOI: 10.1123/jsr.2022-0356
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Light Pressure Instrument-Assisted Soft Tissue Mobilization at Different Rates on Grip Strength and Muscle Stiffness in Healthy Individuals

Abstract: Context: Instrument-assisted soft tissue mobilization (IASTM) is a popular myofascial treatment utilized by health care professionals. Currently, there is a lack of research on the effects of a light pressure IASTM treatment on the forearm region. The purpose of this study was to explore the effects of a light pressure IASTM technique at different application rates on grip strength and muscle stiffness. This study was considered exploratory with the goal of establishing methodology for future controlled studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Thus, IASTM researchers have investigated the effectiveness of light pressure to optimize treatments. Preliminary evidence that IASTM works from a neurophysiological mechanism is supported by findings of modulated grip strength [7] improved tactile discrimination [11] and increased blood flow [26] following light pressure IASTM. While each of these studies demonstrated that lighter forces can be effective, there is also evidence that increased forces stimulate connective tissue remodeling, reduce fascial adhesions, and break down scar tissue that limit ROM [4,27,28].…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Thus, IASTM researchers have investigated the effectiveness of light pressure to optimize treatments. Preliminary evidence that IASTM works from a neurophysiological mechanism is supported by findings of modulated grip strength [7] improved tactile discrimination [11] and increased blood flow [26] following light pressure IASTM. While each of these studies demonstrated that lighter forces can be effective, there is also evidence that increased forces stimulate connective tissue remodeling, reduce fascial adhesions, and break down scar tissue that limit ROM [4,27,28].…”
Section: Discussionmentioning
confidence: 94%
“…Theories for neurophysiological effects from IASTM suggest that activation of lowthreshold mechanoreceptors in the dermis (e.g., Pacinian corpuscles, Meissner corpuscle, Merkle's disks) can be used to modify pain or increase blood flow [7,24,25]. Gentle mechanical forces have been found to stimulate the activation of these mechanoreceptors [24,25] and result in pain relief [24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations